Evaluation of amitraz and derivatives in poisoned cat fur: a new screening method via Headspace/Gas Chromatography-Mass Spectrometry - case report - L.P.T. Prado; J.M.G. Barbosa; M.C. Vicente; A.C.M. Barros; N.M.S. Correia; L.L.P. Silva; B.K. Rodrigues; L.C. David; A.F.M. Botelho; N.R. Antoniosi FILHO (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2025)
ABSTRACT Amitraz is a toxic pesticide that causes severe poisoning in animals; however, few reports of poisoning in cats can be found. Current diagnostic techniques mostly use invasive sampling and require a long time. A new noninvasive technique presented in this report provides accurate diagnosis. Here, we report a case of a 5-year-old male Persian cat with no prior history of illness, presenting vomiting, decreased consciousness, ataxia, and prostration following topical amitraz application for flea control. When admitted to the emergency service, 0.1% of intravenous yohimbine hydrochloride solution was administered to reverse the α-2 adrenergic agonist effects caused by the pesticide. Clinical tests indicated a slight increase in the alanine transaminase (ALT). Furthermore, samples from fur were collected during hospitalization to confirm and follow up the amitraz diagnosis using headspace/gas chromatography-mass spectrometry (HS/GC-MS) analysis. The presence of amitraz in the fur was detected by HS/GC-MS through its derivative products 2,4-dimethylaniline (DMA) and 2,4-Dimethylphenylformamide (DMF). After 24 hours, the patient was released with recommendations to avoid amitraz use and a recommendation for a bath and clipping. Fast aid and antidote administration were decisive factors in the successful treatment. Fur HS/GC-MS stands out as a definitive diagnosis of amitraz poisoning using non-invasive samples.